2016
DOI: 10.1007/s00125-016-4026-0
|View full text |Cite
|
Sign up to set email alerts
|

Early sympathetic islet neuropathy in autoimmune diabetes: lessons learned and opportunities for investigation

Abstract: This review outlines the current state of knowledge regarding a unique neural defect of the pancreatic islet in autoimmune diabetes, one that we have termed early sympathetic islet neuropathy (eSIN). We begin with the findings that a majority of islet sympathetic nerves are lost near the onset of type 1, but not type 2, diabetes and that this nerve loss is restricted to the islet. We discuss later work demonstrating that while the loss of islet sympathetic nerves and the loss of islet beta cells in type 1 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…Given the age-related disparity between rodent and human samples in studies comparing innervation architecture, the dynamic regulation of pancreatic innervation in response to age and environmental influences could be contributing to the observed species differences. Indeed, higher innervation density is observed in human fetal pancreas in comparison to adult ( Proshchina et al, 2014 ), and loss of innervation is observed in humans with Type one diabetes ( Mundinger et al, 2016 ), as it is in several rodent models of autoimmune diabetes ( Mundinger and Taborsky, 2016 ). Studying the dynamic regulation and maintenance of pancreatic innervation could provide a better understanding of diabetes etiology and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Given the age-related disparity between rodent and human samples in studies comparing innervation architecture, the dynamic regulation of pancreatic innervation in response to age and environmental influences could be contributing to the observed species differences. Indeed, higher innervation density is observed in human fetal pancreas in comparison to adult ( Proshchina et al, 2014 ), and loss of innervation is observed in humans with Type one diabetes ( Mundinger et al, 2016 ), as it is in several rodent models of autoimmune diabetes ( Mundinger and Taborsky, 2016 ). Studying the dynamic regulation and maintenance of pancreatic innervation could provide a better understanding of diabetes etiology and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic denervation of islets was reported in three animal models of autoimmune DM as well as in T1DM in people, but not in type 2 DM [11][12][13] , leading to the suggestion that this phenomenon is tightly linked with autoimmune insulitis. This phenomenon has been dubbed eSIN (early Sympathetic Islet Neuropathy) 16 because in contrast to the classic Diabetic Autonomic Neuroparthy (DAN), it precedes the loss of beta cells. We showed that islet sympathetic denervation is a feature of canine DM, but also occurs in canine pancreatitis without DM, suggesting that at least in dogs, it is inflammation in general, not necessarily autoimmunity, that leads to islet neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important not only because they do not lend support to the autoimmune etiology hypothesis in canine DM but also because of their clinical implication. Islet neuropathy is associated with decreased glucagon responses www.nature.com/scientificreports/ in diabetics and inability to respond appropriately to insulin over-dosing which increases the risk and severity of life-threatening hypoglycemia 16 . Our finding that loss of sympathetic innervation is associated with beta cell numbers in canine DM suggests that the risk of hypoglycemia increases with disease duration in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the first phase insulin response with diminished suppression of hepatic glucose production, may be associated with fasting glucose concentrations as low as 5.0‐5.4 mmol/L, and are well described in islet transplant recipients concordant with our observations where a high prevalence of impaired fasting glucose was seen. The mechanism is not known but diminished pulsatility of insulin secretion may play a role . Such studies underline the importance of studying islet transplant participants distinct from other groups with diabetes and extrapolations of data from other subjects with diabetes including those who are C‐peptide positive, may be inappropriate …”
Section: Discussionmentioning
confidence: 99%